Genitourinary brucellosis: results of a multicentric study - Erdem, H.; Elaldi, N.; Ak, O.; Gulsun, S.; Tekin, R.; Ulug, M.; Agalar, C. (Elsevier Sci Ltd, 2014)
This study reviewed the clinical, laboratory, therapeutic and prognostic data on genitourinary involvement of brucellosis in this largest case series reported. This multicentre study pooled adult patients with genitourinary brucellar involvement from 34 centres treated between 2000 and 2013. Diagnosis of the disease was established by conventional methods. Overall 390 patients with genitourinary brucellosis (352 male, 90.2%) were pooled. In male patients, the most frequent involved site was the scrotal area (n=327, 83.8%), as epididymo-orchitis (n=204, 58%), orchitis (n=112, 31.8%) and epididymitis (n=11, 3.1%). In female patients, pyelonephritis (n=33/38, 86.8%) was significantly higher than in male patients (n=11/352, 3.1%; p<0.0001). The mean blood leukocyte count was 7530 +/- 3115/mm(3). Routine laboratory analysis revealed mild to moderate increases for erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP). The mean treatment duration and length of hospital stay were significantly higher when there were additional brucellar foci (p<0.05). Surgical operations including orchiectomy and abscess drainage were performed in nine (2.3%) patients. Therapeutic failure was detected in six (1.5%), relapse occurred in four (1%), and persistent infertility related to brucellosis occurred in one patient. A localized scrotal infection in men or pyelonephritis in women in the absence of leucocytosis and with mild to moderate increases in inflammatory markers should signal the possibility of brucellar genitourinary disease.
Keywords: Brucellae; Brucellosis; epididymoorchitis; genitourinary; orchitis